Technical, perceptual and motor skills in novice-expert water polo players: An individual discriminant analysis for talent development - D'Ercole, A. A.; D'Ercole, C.; Gobbi, M.; Gobbi, F. (The Journal of Strength and Conditioning Research, 2013)
The 4 tasks (A, B, C, and Y) have the characteristic of containing one more element than the task performed before it. In fact, task B introduces the slalom which is not present in task A. Task C introduces the ball control that are not present in tasks A and B, whereas task Y introduces the slalom and ball control in a visual dual task situation developed in horizontal swimming over a distance of 20 m at maximum speed. This exercise not included in task C. These tasks were performed by a group of pre-adolescent players and national under 18 water polo players. The novice players showed that tasks B and C are predictors of task Y. Such characteristics were not present in the expert players. The novice players also had difficulty in performing task Y because of the visual-attention overload, a difficulty that was not present in the expert players. To improve the 4 skills, the coach of the novice players developed a technical-didactic program, which was checked 6 months after the pretest. The posttest was not significantly different from the pretest while the individual discriminant analysis identified the improvements in some novice players, which on elaboration proved significant, enabling us to distinguish 2 subgroups, one with higher learning rates and the other with lower learning rates. In the practical applications, we describe the didactic tools (task analysis) and the different levels of development of technical skills in water polo. Improvements in these skills are explained through computational models like the HMOSAIC (Hierarchical, Modular, Selection and Identification for Control) while the individual discriminant analysis enables us to do a longitudinal analysis that is not possible with cross-sectional models.